Asymptotics of a parabolic problem with a nonsmooth angular function of the boundary layer - Omuraliev, Asan; Abylaeva, Ella (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We construct asymptotic approximations for solving a parabolic problem with nonsmooth angular function of the boundary layer in the case where the perturbation is singular. Unlike the works studied earlier, our algorithm is simple. By choosing a proper regularizing function, we managed to simplify the asymptotic structure of the solution and the construction algorithm. The obtained asymptotics contain only three boundary-layer functions. At the same time, the asymptotics of the solutions constructed earlier contain five boundary-layer components.